Radiation and Scattering of Massive Photons - Saiyan, G. A.
With the aid of a modified Planck’s law for massive photons, it is shown that the ratio of the mean value of the photon mass equivalent to its rest (invariant) mass tends to be one with a decrease in temperature. A modified Stefan - Boltzmann law is obtained at different temperature regimes, as well as the Wien’s displacement law. At high temperatures the modified Planck’ s law approaches the standard Planck’ s law. It is also shown that the cross-section of the Thomson scattering slightly increases opacity of the scattering medium. The Compton shift in frequency for a massive photon appears to be frequency-dependent and slightly less than its value for a massless photon, except in the case of forward scattering when no change in frequency takes place. Astrophysical aspects of the massive photon hypothesis are discussed with regard to standard stellar models, early stages of the Universe, and the Breit-Weeler process, as well as active galactic nuclei. Estimates of the spreading time of the wave packet of the massive photon show that for frequencies ν ≥ 4.052 × 109Hz(λ ≤ 7.4) it exceeds the age of the Universe.
Keywords: Radiation